2013
DOI: 10.1037/a0028609
|View full text |Cite
|
Sign up to set email alerts
|

Influences of spousal support and control on diabetes management through physical activity.

Abstract: Findings suggest that spousal exercise support on its own or in conjunction with spousal exercise control may facilitate daily diabetes management through physical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
129
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(141 citation statements)
references
References 41 publications
11
129
0
Order By: Relevance
“…Indeed, research exploring illness-specific support in couples coping with diabetes has found a sense of “being in this together,” regular communication about the diabetes care regimen, providing encouragement, and joint participation in self-care behaviors are associated with improved patient dietary and exercise adherence (Beverly & Wray, 2010; Khan, Stephens, Franks, Rook, & Salem, in press; Stephens et al, in press). We hypothesize that a general pattern of frequently handling stress by working through problems together and helping each other relax would likely influence patient management of type 2 diabetes, which is conceptualized as one specific stressor couples face (e.g., Schokker et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, research exploring illness-specific support in couples coping with diabetes has found a sense of “being in this together,” regular communication about the diabetes care regimen, providing encouragement, and joint participation in self-care behaviors are associated with improved patient dietary and exercise adherence (Beverly & Wray, 2010; Khan, Stephens, Franks, Rook, & Salem, in press; Stephens et al, in press). We hypothesize that a general pattern of frequently handling stress by working through problems together and helping each other relax would likely influence patient management of type 2 diabetes, which is conceptualized as one specific stressor couples face (e.g., Schokker et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Other research has found moderated effects between spouse coping efforts and patient self-efficacy. A daily diary study found spousal support increased exercise-specific efficacy when high levels of support are accompanied by high levels of control, such as prompting the patient to engage in exercise and monitoring the patient to ensure that he or she exercised (Khan et al, in press). A study of patients diagnosed with type 2 diabetes or asthma found that partners’ not openly communicating worries about the patient’s illness was actually associated with higher patient self-efficacy when patient symptoms were low (de Ridder, Shcreurs, & Kuijer, 2005) and overprotective coping efforts from a spouse were associated with less self-efficacy, especially when glycemic control was poor (Schokker et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…21 Marital status is significant to consider regarding older African American women's chronic illness self-management because research demonstrates that marriage may be a protective factor against poverty for many women 20 and spouses can be an important source of social support for chronic illness self-management. 22,23 A qualitative study conducted with five HIV positive African American women ages 29-49, reveals that women's perceptions of receiving emotional support from their spouses positively contributes to women's HIV coping and self-management strategies. 24 It is also important to note that many older African American women commonly assume traditional gender roles including that of family health manager and often place their health care needs behind the needs of other family members including spouses, children, and grandchildren.…”
Section: Chronic Illness Self-managementmentioning
confidence: 99%
“…On the other hand, family members as a primary source of social support can make great contributions to patients' disease management. To date, only a few studies have shown that spouse's behavior and attitude can affect patient management of diabetes[24], [25], stroke[26], and osteoarthritis[27] rehabilitation therapy. For the dialysis population, although previous studies have indicated the significant impact of social support on satisfaction, psychological status, quality of life, hospitalization, and mortality for PD and HD patients[7][11], the association between a specific aspect of family members, such as education status and PD outcome has rarely been explored.…”
Section: Discussionmentioning
confidence: 99%